A metamodel for competence assessment: Co.S.M.O.© competences software management for organizations. Issue 6 (17th November 2019) - Bellini, Diego; Cubico, Serena; Favretto, Giuseppe; Noventa, Stefano A.; Ardolino, Piermatteo; Gianesini, Giovanna; Ciabuschi, Francesco; Leitao, Joao; Jain, Ajay K.
Abstract : Purpose: This paper aims to propose an explorative metamodel of the key organizational competences management and presents a Web-based tool (Co.S.M.O. © Competences Software Management for Organizations) for all-around assessment of the identified competences. Design/methodology/approach: Building on the Great Eight Competencies Model- GEC, the European Qualifications Framework-EQF and focus group feedback, an online questionnaire was developed to manage the key organizational competences and to adapt the competence metamodel to the Italian context. Findings: The competence metamodel described in this study and its newly designed tool (software with online questionnaire) could be used at the organizational level to improve productivity and efficiency by allowing an easy identification of key organizational competences and facilitating their acquisition and sharing. Research limitations/implications: Currently, the metamodel is mainly theoretical and the software sustained only a partial validation. Practical implications: The developed tool is a dynamic, easy to use and interactive Web-based software useful for managing the competences in both for-profit and not-for-profit organizations. Social implications: European official documents invite companies and institutions to work together and share human capital: the European Qualifications Framework-EQF, at the base of this model, facilitates a common organizational language for human resources management. Originality/value: Managerial competence literature indicates that a comprehensive model capturing a link between the EQF and a managerial competence model has not yet been considered in the literature.